Anadolu'da Dârülhadislerin gelişimi - Uslu, Kevser (My University, 2024)
İslâm dininin eğitime verdiği önem sebebiyle ilmi talep eden Müslümanların sayısının zamanla artmasıyla eğitimin yapılacağı yeni mekânlara ihtiyaç duyulmuştur. Bu durum eğitimde müesseseleşmenin zeminini oluşturmuş ve ilk sistemli eğitim yapıları olan medreselerin inşa edilmesine sebep olmuştur. Medreselerin kurulmasını takip eden dönemlerde ihtisaslaşma düşüncesinden hareketle bazı ilimler özelinde müstakil yapılar kurulmuştur. Dârülhadisler bu durumun neticelerinden biri olarak varlık kazanmış ve dârülhadis ismiyle sistemli ilk yapı Şam’da inşa edilmiştir. İslâm coğrafyası içinde imar edilen hadis eğitim mekânlarını takip eden süreçte Anadolu’da da dârülhadisler kurulmaya başlanmıştır. Anadolu’da inşa edilen dârülhadislerle ilgili çalışmalar hadis ve eğitim alanında yoğunlaşmıştır. İslâm Sanatı içinde teşekkül eden bu mekânların mimari ve tezyîni yönden gelişimini sunan çalışma bulunmamaktadır. Bu çalışmayla Anadolu Selçuklu, İlhanlı ve Osmanlı devrinde Anadolu coğrafyasında inşa edilen dârülhadislerin mimari ve tezyîni özellikleri değerlendirilerek göstermiş olduğu gelişim aktarılmaktadır.

The increasing number of Muslims seeking knowledge over time, due to the emphasis Islam places on education, created a need for new spaces dedicated to learning. This laid the foundation for the institutionalization of education and led to the construction of the first systematic educational structures: madrasas. In the periods following the establishment of madrasas, independent structures were built for specific sciences based on the idea of specialization. Dar al-hadith institutions emerged as a result of this, with the first organized structure named dar al-hadith being built in Damascus. Following the construction of spaces for hadith education throughout the Islamic world, dârülhadis institutions also began to be established in Anatolia. Research on the dar al-hadith institutions built in Anatolia has mainly focused on the fields of hadith and education. However, no study has been conducted on the architectural and decorative development of these structures, which were formed within the context of Islamic art. This study aims to evaluate the architectural and decorative features of the dar al-hadith institutions built in Anatolia during the Anatolian Seljuk, Ilkhanid, and Ottoman periods and to present their development over time.
The development of Dar al-hadıths in Anatolıa
Keywords: Anadolu; Anatolia; Architecture; Dârülhadis; Decoration; Dini eğitim; History; Islamic Art; İslâm Sanatı Dar al-hadith; Madrasah; Madrasahs; Medrese; Medreseler; Mimari; Religious education; Tezyinat